2019
DOI: 10.1111/febs.14749
|View full text |Cite
|
Sign up to set email alerts
|

ITGB4 deficiency induces senescence of airway epithelial cells through p53 activation

Abstract: Aging is characterized by a progressive loss of physiological integrity, leading to impaired organ function and, ultimately, increased vulnerability to death. Many complex diseases are related to aging, including asthma. In the lung, the airway epithelium serves as the first barrier to prevent the access of inspired external stimuli and dictates the initial stress responses. Notably, in the airway mucosa of asthma patients, an increase in senescent airway epithelial cells has been detected. Although it has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…In IPF, we could find out a lot of gene mutations correlating to the premature aging of epithelial cells (Richeldi et al, 2017), while those gene mutations haven't been reported in asthma. Instead, according to current studies, ITGB4 might be a pivotal gene to link epithelial cell senescence and the development of asthma (Liu et al, 2010a,b;Yuan et al, 2019), while it has not been demonstrated in COPD and IPF.…”
Section: Specific Role Of Cellular Senescence In Asthma Different Fromentioning
confidence: 90%
See 1 more Smart Citation
“…In IPF, we could find out a lot of gene mutations correlating to the premature aging of epithelial cells (Richeldi et al, 2017), while those gene mutations haven't been reported in asthma. Instead, according to current studies, ITGB4 might be a pivotal gene to link epithelial cell senescence and the development of asthma (Liu et al, 2010a,b;Yuan et al, 2019), while it has not been demonstrated in COPD and IPF.…”
Section: Specific Role Of Cellular Senescence In Asthma Different Fromentioning
confidence: 90%
“…ITGB4 was also found to be decreased in asthmatic patients (Liu et al, 2010b). Deficiency of ITGB4 could result in cellular senescence in airway epithelial cells through p53 signaling pathway (Yuan et al, 2019). Besides, ITGB4 deficiency could also result in severe airway inflammation and airway hyperresponsiveness in asthma (Liu et al, 2010a).…”
Section: Senescent Cells and Their Influences On The Development Of Amentioning
confidence: 96%
“…Of particular note is the potential role of aging in the parthenogenesis of asthma [28,29]. Many studies have demonstrated the exist of aging structural cells, immune cells and mesenchymal cells in asthmatic lung although the speci c role of aging cells in asthma is still not fully understood [20,30,31]. Meanwhile, some related studies have also con rmed the different expression of aging-related genes (such as TP53 and FOXO3) in the development of respiratory diseases [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Total mRNA was puri ed from peripheral blood cells using Trizol (Invitrogen) and quanti ed by an ultraviolet spectrophotometer (Thermo Fisher Scienti c, USA) [20]. 1μg RNA was reverse transcribed into cDNA using Reverse Transcriptase Kit (Qiagen, Netherlands) accordance to the manufacturer's instructions [21].…”
Section: Rna Extraction and Quantitative Rt-pcrmentioning
confidence: 99%
“…Total mRNA was puri ed from peripheral blood cells using Trizol (Invitrogen) and quanti ed by an ultraviolet spectrophotometer (Thermo Fisher Scienti c, USA) [20]. 1 µg RNA was reverse transcribed into cDNA using Reverse Transcriptase Kit (Qiagen, Netherlands) accordance to the manufacturer's instructions [21].…”
Section: Rna Extraction and Quantitative Rt-pcrmentioning
confidence: 99%